Auditor characteristics and audit report lag: A research from the Indonesian Stock Exchange - Finka Febrianingrum; Fahri Ali Ahzar; Sayekti Endah Retno Meilani; Fitri Laela Wijayati; Wahyu Pramesti (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This study aims to determine the effect of auditor specialists, auditor reputation, auditor gender, auditor education level, and auditor professional certification on audit report lag by using research objects, namely all companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique in this study used a purposive sampling technique. The data analysis used in this study is the Eviews 9 panel data regression analysis software. The results show that the auditor specialist independent variable has a negative effect on audit report lag. Meanwhile, auditor reputation, auditor gender, and auditor education level do not effect audit report lag. The professional certification of auditors has a positive effect on audit report lag. Meanwhile, the addition of control variables, namely firm size and loss, has a positive effect on audit report lag. However, the control variable ROA has a negative effect on audit report lag.